2020
DOI: 10.1101/2020.09.05.20188912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beneficial and harmful outcomes of tocilizumab in severe COVID-19: a systematic review and meta-analysis

Abstract: Background: Pending for randomized control trials, the use of tocilizumab (TCZ) in COVID-19 is based on observational studies and remains controversial. Purpose: To summarize evidence about the effect of TCZ to treat severe COVID-19. Data sources: PubMed (via MEDLINE), Scopus, and medRxiv repository databases from 1 January to 21 August 2020. Study Selection: Observational studies in any language reporting efficacy and safety outcomes of TCZ use in hospitalized adults with COVID-19. Data Extraction: Indep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Similar results were obtained by previous meta-analysis studies on the effect of tocilizumab treatment on the mortality risk of COVID-19 patients. Khan et al [ 87 ], Rubio-Rivas et al [ 88 ], and Kotak et al [ 89 ] reported RRs [95%CIs] of 0.83 [0.72, 0.96], 0.73 [0.57, 0.93], and 0.56 [0.34, 0.92], respectively, and Zhao et al [ 90 ] and Sarfraz et al [ 91 ] reported odds ratios [95%CIs] of 0.44 [0.36, 0.55] and 0.42 [0.26, 0.69], respectively, with tocilizumab treatment compared with SOC. Despite the promising results in these meta-analysis studies, none of the four published RCTs found a significant beneficial effect on mortality rates for tocilizumab in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by previous meta-analysis studies on the effect of tocilizumab treatment on the mortality risk of COVID-19 patients. Khan et al [ 87 ], Rubio-Rivas et al [ 88 ], and Kotak et al [ 89 ] reported RRs [95%CIs] of 0.83 [0.72, 0.96], 0.73 [0.57, 0.93], and 0.56 [0.34, 0.92], respectively, and Zhao et al [ 90 ] and Sarfraz et al [ 91 ] reported odds ratios [95%CIs] of 0.44 [0.36, 0.55] and 0.42 [0.26, 0.69], respectively, with tocilizumab treatment compared with SOC. Despite the promising results in these meta-analysis studies, none of the four published RCTs found a significant beneficial effect on mortality rates for tocilizumab in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tocilizumab which blocks IL-6 receptor is also proposed [4] with intravenous use being suggested to be superior to subcutaneous administration [42] . Although the ROCHE press release of the first results from the phase III COVACTA trial is not favouring early administration in all patients, some systematic reviews suggest potential mortality benefit in some cohorts with acute respiratory failure [43] . Sarilumab is also effective in blocking IL-6 receptors and may have similar effects.…”
Section: Covid-19 Managementmentioning
confidence: 99%
“…However, based on experience from the pre-COVID era, TCZ carries a “black box” warning for serious infection events (SIEs; Figure 1B ) caused by a range of opportunistic bacterial, mycobacterial, viral and fungal pathogens that may lead to hospitalisation or death. Pooled analyses of the SIE risk associated with the standard dose have estimated incidence at ~5 per 100 patient years ( 21 , 22 ), similar to other biologic drugs ( 1 ), but with higher risk in older adults, in combination with steroids and/or methotrexate ( 23 25 ), or with previous biologic therapy ( 26 ). Such SIEs can be related to the impairment of IL-6 activity in co-ordinating diverse immune responses, including activation of neutrophils and lymphocytes, acute phase protein production and tissue repair ( Figure 2 ) ( 2 ).…”
Section: Introductionmentioning
confidence: 99%